2016
DOI: 10.1186/s12894-016-0171-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of CDH13 promoter methylation as a biomarker for bladder cancer: a meta-analysis

Abstract: BackgroundMethylation of the tumor suppressor gene H-cadherin (CDH13) has been reported in many cancers. However, the clinical effect of the CDH13 methylation status of patients with bladder cancer remains to be clarified.MethodsA systematic literature search was performed to identify eligible studies in the PubMed, Embase, EBSCO, CKNI and Wanfang databases. The pooled odds ratio (OR) and the corresponding 95 % confidence interval (95 % CI) was calculated and summarized.ResultsNine eligible studies were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In addition, CDH13 can induce the reversion of morphology from an invasive to a normal cell-like type. In a previous study, downregulated CDH13 protein expression was found in bladder TCC ( 26 ). However, the effects and mechanisms of downregulated CDH13 expression on bladder TCC invasion need to be further elucidated.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, CDH13 can induce the reversion of morphology from an invasive to a normal cell-like type. In a previous study, downregulated CDH13 protein expression was found in bladder TCC ( 26 ). However, the effects and mechanisms of downregulated CDH13 expression on bladder TCC invasion need to be further elucidated.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, an association between the abnormal expression of CDH13 and its promoter methylation in lung cancer has been demonstrated ( 22 – 24 ). Recent studies have reported that CDH13 functioned as an anti-oncogene in lung ( 1 ), breast ( 25 ), ovarian ( 3 ), bladder ( 26 ), esophageal ( 27 ) and gastric cancer ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…The hypermethylation of the ADHFE1 promoter in colorectal cancer has recently been demonstrated [ 64 , 65 ]. CDH13 promoter methylation has been identified as a biomarker for bladder cancer [ 66 ]. Recently, ENG promoter hypermethylation was reported in several human cancers [ 67 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…In ALL, TP53 mutations are rather infrequent. In childhood B-ALL and pediatric T-ALL the reported prevalence is 2–5% of cases [ 24 , 25 ], whilst in adult patients it is 6.4–11.1% of cases [ 26 ]. On the other hand, TP53 mutations occur in 15.7% of ALL cases, which increases with age.…”
Section: Discussionmentioning
confidence: 99%